Pelaksanaan Parate Eksekusi Dalam Jaminan Fidusia Di Indonesia - Farid Hardianysah (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Developments in guarantee law always evolve over time. The law of guarantees is very closely related to the implementation of credit, lending and borrowing or as repayment of debts between creditors and debtors. In its legal aspect, control over objects that serve as collateral for a debt gives birth to material rights that provide privileges to creditors in the event that the debtor is unable to pay obligations while at the same time providing legal protection to creditors in carrying out their debts. Law Number 42 of 1992 concerning Fiduciary Guarantees provides a legal basis regarding the implementation of guarantees as guarantees for repayment of debts from debtors. The enactment of the law regarding fiduciary guarantees is expected to provide proportionality between debtors and creditors. In its development, the implementation of execution in the context of fiduciary guarantee law through the Constitutional Court Decision Number 2/PUU-XIX/2021 which is a form of explanation as well as confirmation of the Constitutional Court Decision 18/PUU-XVII/2019 regarding the application of execution of fiduciary guarantees has had legal implications in society . Based on the Constitutional Court's decision which created a new norm in the context of executing fiduciary guarantees, it directly changes the procedures and conditions that must be met for the execution of parate execution by creditors in the event that the debtor acknowledges default and voluntarily surrenders the object of fiduciary collateral so that it is expected can realize the principles of legal certainty, justice and benefit within the framework of the principle of proportionality between debtors and creditors in the practice of Fiduciary Guarantees.